PROFILE OF STUDENTS’ ANALOGICAL REASONING IN SOLVING MATHEMATICS PROBLEMS: A STUDY BASED ON SELF-REGULATED LEARNING - Mar'atus Solehah; Masriyah Masriyah (MATHEdunesa, 2021)
Analogical reasoning is an important ability for students related to reasoning activities by thinking carefully about the regularity of patterns found in mathematics. One of the factors that influence analogical reasoning is self-regulated learning, which shows the ability of the student to analyze, take strategies, and the ability to control their learning environment. This research aims to describe students’ analogical reasoning in solving mathematics problems based on self-regulated learning. The subjects were one student with low self-regulated learning and one student with high self-regulated learning. The research method used is descriptive qualitative, and data were obtained through analogical problem-solving tests and interviews. Subjects were chosen based on the questionnaire instruments’ categorization regarding the student's self-regulated learning and the mathematical ability test instruments. The results of this study were (1) Analogical reasoning of a student with low self-regulated learning: passed through the stages of structuring, mapping, and applying. At the structuring, the student identified all the information completely, but did not understand the problem correctly and could found the relationship between the source problem and the target problem. At the mapping stage, the mapping process only appears in the student’s mind. At the applying stage, not completely mentioned all the possible solutions to the given problems. Meanwhile, (2) Analogical reasoning of a student with high self-regulated learning passed all the analogical reasoning stages of structuring, mapping, applying, and verifying. At the structuring, the student identified all the information completely and understand the problem. At the mapping stage, the student built a new mathematical model for the target problem. At the applying, the student mentioned all the possible solutions correctly. And student did the verification. Keywords: analogical reasoning, self-regulated learning, problem-solving